Pengaruh Motivasi terhadap Kinerja Guru SMP Negeri Kecamatan Bangkinang Kota Kabupaten Kampar - FARWITAWATI, RENI; FITHRIE, SOUVYA (Jurnal Daya Saing, 2017)
Abstract: This research aims to understand the the influence of motivation on the performance of employees at educational institutions at Bangkinang the district capital of Kampar. Type research which is located in public junior high schools Bangkinang the district capital of Kampar is descriptive with a quantitative approach, namely prioritise questions list as a means of data collection and data collected with this device then used as the main raw empirical analyze the condition of the existence of a purpose objektifitas research on the site of minutely. The population of this study is all all teachers in state schools Bangkinang the district capital of Kampar .The research is empirical research with using a technique purposive of sampling in the sample collection criteria teachers in state schools Bangkinang the district capital of Kampar that had been certified by the year 2016/ 2017. Of the population which consisted of 150 people, then meet the criteria of a samples from 80 people plus 3 respondents supporting such as 1 people the education office and 2 supervisors school. Data is collected by spreading the questionnaire 80th respondents and interview to 3 respondents supporting. Than 80 the questionnaires returned all (100 %). Based on technique analysis a correlation coefficient of 0,567, the coefficients determination 0,322 and results of the test t and significance <0.05 then the researcher judging and inferring that is the motivation of the performance of teachers. Keywords: Motivation, employee performance, Educational Institutions